Canhotos: representações sociais de jovens sobre uma diferença invisível - Costa, Priscila Lambach Ferreira da (2023)
The left-hander can be defined as the one who has preference for the left side of the body to perform activities. It represents around 10% of the population and is present in all schools around the world. However, often these students do not find the proper physical and attitudinal conditions for their full development. It is admitted that not all schools have adequate furniture and material to meet the left-handed student in the specificity. The aim of this research is to unsee the social representations of young people about the left-handed person and propose alternatives of educational practices for their inclusion. To this end, a comprehensive survey of research on left-handedness, social representations and social representations about inclusion was conducted. In addition to the bibliographic and integrative review, an initial pilot study was carried out applying questionnaires with teachers and left-handed students from 6 to 17 years old in a public school of a municipality near São Paulo. As a result, it was found that students consider that the left-hander has more ease and skill for performing some tasks, has the most beautiful handwriting, is special, fun, different and cool. Teachers constantly ignore who the left-handed students are and are unaware of their needs. Subsequently, a field study was carried out proposing an experience with specific materials for left-handers (scissors, ruler, sharpener, pen, pencil, and crayon) followed by a conversation wheel and online questionnaire with a group of five young people from 15 to 20 years old in the community of Paraisópolis in São Paulo, four right-handed and one left-handed. The young people knew little about the subject and reported difficulty in using the materials and that this made them have empathy towards the left-handers by understanding them better. Participants from both territories reported understanding the importance of schools and families providing materials that make the school life of the left-handed student more favorable. It can be insured that deletion, invisibility, exclusion are complex concepts that permeate the issue of left-handedness, ordering a theoretical lens capable of apprehending this theme, full of challenges. Therefore, we chose to illuminate the research problem by the Theory of Social Representations, because social representations can be seen as a resource for groups to recognize themselves, differentiate themselves and certainly contribute to the construction of social identity. Its relevance is understood to deepen the issue of left-handedness because it is a structure that involves, in addition to information or content on a given theme or object of representations, attitudes and values